Diagnostic performance of commercial IgM and IgG enzyme-linked immunoassays (ELISAs) for diagnosis of Zika virus infection - Kikuti, Mariana (2018)
Background: Serologic detection of Zika virus (ZIKV) infections is challenging because of antigenic similarities among flaviviruses. Objective: To evaluate the sensitivity and specificity of commercial ZIKV IgM and IgG enzyme-linked immunoassay (ELISA) kits. Methods: We used sera from febrile patients with RT-PCR-confirmed ZIKV infection to determine sensitivity and sera from RT-PCR-confirmed dengue cases and blood donors, both of which were collected before ZIKV epidemics in Brazil (2009-2011 and 2013, respectively) to determine specificity. Results: The ZIKV IgM-ELISA positivity among RT-PCR ZIKV confirmed cases was 0.0% (0/14) and 12.5% (1/8) for acute- and convalescent-phase sera, respectively, while its specificity was 100.0% (58/58) and 98.3% (58/59) for acute- and convalescent-phase sera of dengue patients, and 100.0% (23/23) for blood donors. The ZIKV IgG-ELISA sensitivity was 100.0% (6/6) on convalescent-phase sera from RT-PCR confirmed ZIKV patients, while its specificity was 27.3% (15/55) on convalescent-phase sera from dengue patients and 45.0% (9/20) on blood donors' sera. The ZIKV IgG-ELISA specificity among dengue confirmed cases was much greater among patients with primary dengue (92.3%; 12/13), compared to secondary dengue (7.1%; 3/42). Conclusions: In a setting of endemic dengue transmission, the ZIKV IgM-ELISA had high specificity, but poor sensitivity. In contrast, the ZIKV IgG-ELISA showed low specificity, particularly for patients previously exposed to dengue infections. This suggests that this ZIKV IgM-ELISA is not useful in confirming a diagnosis of ZIKV infection in suspected patients, whereas the IgG-ELISA is more suitable for ZIKV diagnosis among travelers, who reside in areas free of flavivirus transmission, rather than for serosurveys in dengue-endemic areas.